SIKAP PENGOLAH DALAM MENENTUKAN PRODUK IKAN ASIN - Ernik Yuliana (Jurnal Pengolahan Hasil Perikanan Indonesia, 2012)
Salted fish products produced by processors in Muara Angke and Cilincing are very diverse on size and type. Choosing of types of salted fish to be produced by processors depends on some factors. The purpose of this study was to identify the factors which related with processors attitude on choosing salted fish product. The research design was exploratory research. The population were all of the salted fish processors in Muara Angke and Cilincing, North Jakarta. Respondences were choosen randomly to get 73 salted fish processors, 55 persons of them were located at Muara Angke and another 18 were from Cilincing.  Data collected consist of primary data which used survey methods. Then data were analysed using descriptive-analysis and Rank Spearman correlation. The results indicated that the most preferred salted fish product by processors were small fish types, i.e fringerscales sardinella, anchovy and squid, because of of raw materials. Processors’ continuity of raw materials. attitude on choosing of salted fish product was significantly corrrelated with processors’ obedience to the rule of processing norms/customs regulations.Key words: access of processing technology, salted fish products, processors’ attitude